2019
DOI: 10.3847/1538-4357/ab2871
|View full text |Cite
|
Sign up to set email alerts
|

On the Pitch-angle-dependent Perpendicular Diffusion Coefficients of Solar Energetic Protons in the Inner Heliosphere

Abstract: Various numerical solar energetic particle (SEP) transport studies have shown that perpendicular diffusion plays a significant role in the propagation of these particles in the heliosphere. In particular, computed SEP intensities and anisotropies have been shown to be sensitive to the pitch-angle dependence of the perpendicular diffusion coefficient as well as its magnitude. This study proposes a novel approach to the calculation of this quantity and compares this to the results of previous theoretical approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…High-cadence magnetic field observations made by the Parker Solar Probe (PSP) during its various perihelia provide us with an unprecedented opportunity to study the radial evolution of various quantities associated with the dissipation of solar wind turbulence (see, e.g., Woodham et al 2019;Perrone et al 2020;Alexandrova et al 2021;Chhiber et al 2021a), motivated by the fact that a greater understanding of the processes of kinetic dissipation in magnetized plasma is essential for explaining the physical origin and evolution of the solar wind (e.g., Bruno & Carbone 2016;Duan et al 2020;Matteini et al 2020;Telloni et al 2021;Zhao et al 2022a). This, in turn, also informs modeling efforts of turbulence transport (e.g., Engelbrecht & Strauss 2018;Chhiber et al 2019;Adhikari et al 2020Adhikari et al , 2021a and energetic particle transport (e.g., Strauss et al 2017;Engelbrecht 2019;Laitinen & Dalla 2019;Chhiber et al 2021b) and relates to density turbulence that is important for solar radio burst interpretation (e.g., Krupar et al 2020;Kontar et al 2019). Magnetic field fluctuations in the solar wind are commonly observed to follow a power-law spectrum.…”
Section: Introductionmentioning
confidence: 71%
“…High-cadence magnetic field observations made by the Parker Solar Probe (PSP) during its various perihelia provide us with an unprecedented opportunity to study the radial evolution of various quantities associated with the dissipation of solar wind turbulence (see, e.g., Woodham et al 2019;Perrone et al 2020;Alexandrova et al 2021;Chhiber et al 2021a), motivated by the fact that a greater understanding of the processes of kinetic dissipation in magnetized plasma is essential for explaining the physical origin and evolution of the solar wind (e.g., Bruno & Carbone 2016;Duan et al 2020;Matteini et al 2020;Telloni et al 2021;Zhao et al 2022a). This, in turn, also informs modeling efforts of turbulence transport (e.g., Engelbrecht & Strauss 2018;Chhiber et al 2019;Adhikari et al 2020Adhikari et al , 2021a and energetic particle transport (e.g., Strauss et al 2017;Engelbrecht 2019;Laitinen & Dalla 2019;Chhiber et al 2021b) and relates to density turbulence that is important for solar radio burst interpretation (e.g., Krupar et al 2020;Kontar et al 2019). Magnetic field fluctuations in the solar wind are commonly observed to follow a power-law spectrum.…”
Section: Introductionmentioning
confidence: 71%
“…Engelbrecht et al [193] calculated the galactic cosmic ray electron intensities using the observed size of magnetic islands [195,196], and different outer scales [136,145], finding that galactic cosmic ray electron differential intensities above kinetic energy 0.1 GeV are closer to the observed electron differential intensities, and lower than that below 0.1 GeV. Similarly, Engelbrecht et al [194] proposed a new method to calculate the perpendicular diffusion coefficients by using the random ballistic decorrelation interpretation of the NLGC theory proposed by Ruffolo et al [197]. The results show that the strength and anisotropy of solar energetic particle (SEP) are very sensitive to the pitch-angle dependence of the perpendicular diffusion coefficient.…”
Section: Cr Perpendicular Mean Free Pathmentioning
confidence: 89%
“…The 2D turbulence power spectrum behavior at the lowest wavenumber, i.e., the outer scale, has an important impact on the perpendicular diffusion coefficients of charged particles in the heliosphere [146,193,194], including galactic cosmic ray proton and electron intensities. Engelbrecht et al [193] calculated the galactic cosmic ray electron intensities using the observed size of magnetic islands [195,196], and different outer scales [136,145], finding that galactic cosmic ray electron differential intensities above kinetic energy 0.1 GeV are closer to the observed electron differential intensities, and lower than that below 0.1 GeV.…”
Section: Cr Perpendicular Mean Free Pathmentioning
confidence: 99%
“…This is, of course, not unexpected for SEP transport, where a highly anisotropic particle distribution is formed. This remains an ongoing topic of investigation, both theoretically (Strauss et al 2016;Engelbrecht 2019;Shalchi 2020) and from numerical simulations Shalchi 2009, 2014).…”
Section: Effect Of Perpendicular Diffusionmentioning
confidence: 99%